The Public Relations Role Towards the Success of Waste Collecting Point Program in Banda Aceh - Zakirah Azman; Deni Yanuar; Munawir Syarif (Calathu: Jurnal Ilmu Komunikasi, 2021)
This study attempted to determine the role of Public Relation (PR) of Banda Aceh’s Environmental, Cleanliness, and the Beauty of the City Agency on the “Waste Collecting Point (WCP) program. The theory used was role theory developed by Redfield, Linton, and Herskovits. The method which was being used wasdescriptive qualitative, which the subject of the study was PR division and societies. The finding showed that PR division played a very important role in the success of Waste Collecting Point (WCP) program from the beginning until the outcome being shown on the cleanliness of the districts. Starting from the socialization process, the program showed significant success. Persuasive communication was being used to conduct the program. PR division made initial socialization by informing the societies about the danger of the waste if not managed properly then followed by monthly evaluation on the cleaning leader. Keywords: Public Relation, role theory, waste collecting point, Banda Aceh